Defining recovery potential in river restoration: a biological data-driven approach - Wilkes, Martin A.; Mckenzie, Morwenna; Naura, Marc; Allen, Laura; Morris, Mike; Van De Wiel, Marco; Dumbrell, Alex J.; Bani, Alessia; Lashford, Craig; Lavers, Tom; England, Judy (MDPI, 2021)
Scientists and practitioners working on river restoration have made progress on understanding the recovery potential of rivers from geomorphological and engineering perspectives. We now need to build on this work to gain a better understanding of the biological processes involved in river restoration. Environmental policy agendas are focusing on nature recovery, reigniting debates about the use of “natural” reference conditions as benchmarks for ecosystem restoration. We argue that the search for natural or semi-natural analogues to guide restoration planning is inappropriate due to the absence of contemporary reference conditions. With a catchment-scale case study on the invertebrate communities of the Warwickshire Avon, a fifth-order river system in England, we demonstrate an alternative to the reference condition approach. Under our model, recovery potential is quantified based on the gap between observed biodiversity at a site and the biodiversity predicted to occur in that location under alternative management scenarios. We predict that commonly applied restoration measures such as reduced nutrient inputs and the removal of channel resectioning could be detrimental to invertebrate diversity, if applied indiscriminately and without other complementary measures. Instead, our results suggest considerable potential for increases in biodiversity when restoration measures are combined in a way that maximises biodiversity within each water body
Keywords: river restoration; biodiversity; ecosystem assessment; recovery potential; data-driven